Family Conflict Management and Family Dispute Resolution on Marriage Breakdown and Divorce: Diverse Options - Payne, Julien (Revue générale de droit, 1999)
Family law is only one piece of the puzzle as separating and divorcing couples attempt to manage the conflict and deal with the practical problems arising on marriage breakdown. Divorce is a process, not an event. It is multi-faceted. The emotional dynamics of marriage breakdown may require a time consuming therapeutic response but parenting and economic arrangements must be resolved expeditiously. There is a tendency to assume that spouses who are locked in conflict will find themselves in court. In reality, fewer than four per cent of divorces proceed to trial. The costs of litigation are far too high, both financially and emotionally. Most disputes are resolved by negotiation, often with the assistance of lawyers. If negotiations are to bear fruit at a manageable cost to family members, hard bargaining that reflects "a winner take all" mentality must be avoided; principled negotiation, as espoused by Roger Fisher, William Ury and Bruce Patton in Getting To Yes, can generate optimal results for all interested parties, including the children. Recent years have witnessed the growth of mediation, whereby a neutral third party assists family members in searching for consensus on matters in dispute. The mediator controls the process but the family members control the substantive outcome of their deliberations. Mediation is nothing more than structured negotiation where a third party facilitates resolution of the dispute. If a final settlement cannot be reached, one possible option is recourse to private arbitration in which a third party is given the authority to determine the respective rights and obligations of the spouses and their children. It is possible to combine the aforementioned processes for the purpose of reaching a complete settlement of matters in dispute. These processes are complementary to the judicial process and should be closely examined by all families faced by the cataclysmic disruption generated by a failed marriage.